Reflective interviewing : a guide to theory and practice - Roulston, Kathryan (Sage publications, London, 2010)
This book offers a comprehensive guide for researchers learning to conduct interviews in the social sciences. It goes beyond practical advice on designing and conducting interviews, delving into the theoretical underpinnings of different interview approaches and their epistemological assumptions. By exploring the researcher's role and subjectivity, the book encourages reflective practice and helps researchers understand how their own perspectives shape the interview process and the resulting data. This insightful work is essential for both novice and experienced researchers seeking to improve their interview skills and deepen their understanding of this crucial research method.
Includes appendix bibliographical references (p. 190-204) and index.
Keywords: Qualitative research methods; Interviewing : qualitative research; Social sciences; Epistemology